The fate of Communion: the agony of Anglicanism and the future of a global church - Radner, Ephraim (William B. Eerdmans Pub. Co, 2006)
Introduction : unity, obedience, and the shape of communion -- The challenge of the present moment -- The end of a church and the triumph of denominationalism : on how to think about what is happening in the Episcopal Church -- Children of Cain : the oxymoron of American Catholicism -- Questions of authority -- Apprehending the truth : Anglican conservatism and common discernment -- The scriptural community : authority in Anglicanism -- Diversity and integrity : the challenges of life together -- Episcopal authority within a Communion of churches -- Questions of Communion -- The Virginia report : how firm a foundation? -- The Windsor report : a defining moment for a worldwide Communion -- Conciliarity and the American evasion of Communion -- The future of Communion -- ECUSA's god and the idols of liberal Protestantism -- The humiliation of Anglicanism and Christian life -- Conclusion: The world is waiting for holiness